(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
We give a new map named (Rabinovich-Fabrvikant equations) and find five fixed points we study only one fixed point x0(0,0,0), and all general properties of them We prove that the contracting and expanding area of this point , thought the study of the chaotic of the point by use the Wiggins defined and we proof that the lyapunov exponent of the point (0,0,0) is positive .We use matlab program to show sensitive dependence on the initial conditions and transitivity of (R-F).